PENERAPAN MANAJEMEN DALAM PENGEMBANGAN HASIL LAUT YANG BERDAMPAK PADA KESEJAHTERAAN MASYARAKAT PULAU SERIBU - Moh Sutoro; Sugiyanto Sugiyanto; Yayan Sudaryana; Ugeng Budi Haryoko (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of Community Service (PKM) is to find out how much the application of management in the development of marine products that have an impact on the welfare of local communities. The measurement method uses three approaches including (1) phenomenalogical research method where qualitative methods can be interpreted as a method based on the philosophy of postpositivism used in object conditions, where the researcher as a key instrument, data collection techniques are carried out by triangulation (combined) the results of the analysis is inductive which is to suppress the meaning of Creswell 2009 generalization (in his book Sugiyono 2017: 24), (2) The grounded theory method of this research is a type of qualitative method, in which the researcher draws on the generalization observed inductively, (3) Ethnography Method is Qualitative Strategy menrurut (Crewell 2209) states one type of qualitative research is that researchers conduct group culture studies through interview observation. The results of observations and interviews and training on community service are very potential fisheries subsector commodities, from the high demand for sustainable fish supply. Results of assistance to management in the development of marine fish culture management (sea farming) to increase community income in the Thousand Islands, Jakarta, Development of results need to be formed cooperatives or business units, in an effort to increase community income in the thousand islands.Keywords: Management, Yield Development, and Welfare.